1982
DOI: 10.1002/ijc.2910300314
|View full text |Cite
|
Sign up to set email alerts
|

Glutaminase‐free asparaginase from vibrio succinogenes: An antilymphoma enzyme lacking hepatotoxicity

Abstract: Microbiology 04-4 and Pathology R-1, Miami, FL. USA.Successful treatment of neoplastic disease has been impeded by the lack of therapeutic agents which specifically destroy tumor cells. Enzymes which selectively deplete substrates required by tumor cells, but not by normal tissue, could improve therapeutic indices dramatically. Presently, microbial asparaginases are used clinically for treating acute lymphocytic leukemia. While these enzymes should destroy neoplastic cells and spare normal tissues, their use i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
3

Year Published

1988
1988
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 20 publications
0
44
0
3
Order By: Relevance
“…The purification of enzyme was carried out by using crude enzyme extract (Distasio et al, 1982).The enzyme purification was performed by ammonium sulphate precipitation. Finely powdered ammonium sulfate was added to the crude extract.…”
Section: Purification Of L-asparaginasementioning
confidence: 99%
“…The purification of enzyme was carried out by using crude enzyme extract (Distasio et al, 1982).The enzyme purification was performed by ammonium sulphate precipitation. Finely powdered ammonium sulfate was added to the crude extract.…”
Section: Purification Of L-asparaginasementioning
confidence: 99%
“…K+independent plant L-Asparaginases were reported by Michalska and coworkers. [41] They found that the αβ subunits arise from auto-proteolytic cleavage of two copies of precursor protein and the heterodimer is in αββα configuration. Thr193 acts as the nucleophile and is part of the active site.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
“…[9] L-asparaginase with two distinct bands of molecular weights 40.2 and 39.8 kDa were purified from Erwinia carotovora MTCC 1428. [41] A three step puridfication of asparaginase has also been described. Crude extract was precipitated by 70% ammonium sulphate after which further purification was carried out with Sephadex G-200 using HPLC system.…”
Section: Purification Of L-asparaginasementioning
confidence: 99%
“…While Roberts et al [21] isolated Achromobacteraceae from the soil samples and observed that this family has L-glutaminase and L-asparaginase activity in a ratio of 1.2:1. There are also many reports on the production of the intracellular L-asparaginase as observed from E. aroideae [34] E.carotovora [35] Serratia marcescens [36] ,Vibrio succinogenes [37], E. coli [38], Pseudomonas7A (Jakob et al, 1996) [39] and P.fluorescens [40].…”
Section: Bacterial Amidasesmentioning
confidence: 99%